2020
DOI: 10.1037/aap0000183
|View full text |Cite
|
Sign up to set email alerts
|

Mental health help-seeking intentions among Chinese international students in the U.S. higher education system: The role of coping self-efficacy, social support, and stigma for seeking psychological help.

Abstract: This study investigated the mental health help-seeking intentions and its correlates among Chinese international students in the U.S. higher education system. An analytic cross-sectional study was conducted. Recruitment of participants occurred via a social media campaign, and participants were invited to complete an online anonymous survey. A total of 222 Chinese international students participated in the study. The majority of the participants were female (65.3%), graduate students (84.7%), and the only chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 61 publications
3
44
0
Order By: Relevance
“…Overall, our third domain revealed the critical role of social support in the lives of international students enrolled in a Christian university. This finding is consistent with prior literature that has shown that social support is pivotal to international students’ welfare and contentment during their time in the United States (Lian et al, 2020).…”
Section: Resultssupporting
confidence: 93%
“…Overall, our third domain revealed the critical role of social support in the lives of international students enrolled in a Christian university. This finding is consistent with prior literature that has shown that social support is pivotal to international students’ welfare and contentment during their time in the United States (Lian et al, 2020).…”
Section: Resultssupporting
confidence: 93%
“…Secondly, the newer keywords on the science mapping also showed a stronger emphasis on modern issues that students are facing during their study: the focus on changes in the environment and behavioral problems such as problematic social media use [ 2 , 92 , 93 ], social drinking and gambling [ 38 ], [ 90 , 94 ] has increased in recent years. Environmental changes and adaptation problems such as COVID-19 [ 9 , 91 , 95 ], coping strategies [ 96 , 97 , 98 ], and homesickness [ 68 , 99 ] are also being emphasized. It can also be noticed that, in contrast to the purple nodes, which clustered around the top of the map, the light green nodes were distributed evenly around the map.…”
Section: Resultsmentioning
confidence: 99%
“…However, they occasionally felt helpless owing to the prevalent mental health stigma and mistrust against the public health system in the community. While public-and self-stigma have been previously found to impact self-efficacy among those suffering from a mental illness (Jahn et al, 2020;Lian et al, 2020), this needs to be further studied among mental health care providers. Secondly, the trainings helped ASHAs garner knowledge and skills to undertake mental health task-sharing-related tasks, and receiving support from their supervisors enhanced their efficacy.…”
Section: The Interaction Of Task Demands Resources Availability and Contextmentioning
confidence: 99%